The Local Entertainment Tax and the Federal Financial Equalisation System in Germany - Michael Broer (Wirtschaftsdienst)
Abstract In the past, the federal constitutional court has made judgments about the federal financial equalisation system in Germany, including about taxes should be part of the redistribution of the federal financial equalisation system. The court has developed some criteria e.g. the revenue at all and the per capita revenue. These criteria can be used to compare some taxes that are actually part of the redistribution of the federal financial equalisation system (e.g. beer, gaming casinos and fire protection taxes), with the local slot machine tax (a type of entertainment tax) that is not yet part of the federal financial equalisation system. The comparison shows that the local slot machine tax should be part of the federal system because its revenue is much higher than the revenue of the beer or fire protection tax.